Food Democracy for All? Developing a Food Hub in the Context of Socio-Economic Deprivation - Prost, Sebastian (2019)
This article proposes a localised and differentiated understanding of food democracy, or rather a plurality of localised food democracies. Based on the experiences of developing a local food hub in an area of socio-economic deprivation in the UK using a participatory action research (PAR) approach, it presents local responses to three key challenges derived from the literature. It argues that for civic food networks (CFNs) to contribute to a transition towards a food democracy, they need to address challenges of: 1) balancing ethical aspirations for environmental sustainability, social justice, as well as community and individual health; 2) developing the skills required for participation in CFNs; and 3) achieving wider impact on food system transformation beyond niche solutions. The responses, or tactics, presented in this article include flexible ethical standards responding to community needs, accessible participation focusing on relationships rather than skills, and a focus on local impact while striving to collaborate and network with other organisations. It thus frames food democracy as a plurality of approaches to build and replicate CFNs. The article positions PAR with its democratic and localised approach to address real-world problems as uniquely suited to navigate the challenges of CFNs. It also discusses the role of researchers in initiating, facilitating, and shaping such processes of food system democratisation as engaged actors.